Distinct gene dysregulation patterns herald precision medicine potentiality in systemic lupus erythematosus. Issue 136 (April 2023) - Lindblom, Julius; Toro-Domínguez, Daniel; Carnero-Montoro, Elena; Beretta, Lorenzo; Borghi, Maria Orietta; Castillo, Jessica; Enman, Yvonne; Mohan, Chandra; Alarcón-Riquelme, Marta E.; Barturen, Guillermo; Parodis, Ioannis; ,
Abstract: Objectives: We aimed at investigating the whole-blood transcriptome, expression quantitative trait loci (eQTLs), and levels of selected serological markers in patients with SLE versus healthy controls (HC) to gain insight into pathogenesis and identify drug targets. Methods: We analyzed differentially expressed genes (DEGs) and dysregulated gene modules in a cohort of 350 SLE patients and 497 HC from the European PRECISESADS project (NTC02890121), split into a discovery (60%) and a replication (40%) set. Replicated DEGs qualified for eQTL, pathway enrichment, regulatory network, and druggability analysis. For validation purposes, a separate gene module analysis was performed in an independent cohort (GSE88887). Results: Analysis of 521 replicated DEGs identified multiple enriched interferon signaling pathways through Reactome. Gene module analysis yielded 18 replicated gene modules in SLE patients, including 11 gene modules that were validated in GSE88887. Three distinct gene module clusters were defined i.e., "interferon/plasma cells", "inflammation", and "lymphocyte signaling". Predominant downregulation of the lymphocyte signaling cluster denoted renal activity. By contrast, upregulation of interferon-related genes indicated hematological activity and vasculitis. Druggability analysis revealed several potential drugs interfering with dysregulated genes within the "interferon" and "PLK1 signaling events" modules. STAT1 was identified as the chief regulator in the most enriched signaling molecule network. Drugs annotated to 15 DEGs associated with cis -eQTLs included bortezomib for its ability to modulate CTSL activity. Belimumab was annotated to TNFSF13B (BAFF) and daratumumab was annotated to CD38 among the remaining replicated DEGs. Conclusions: Modulation of interferon, STAT1, PLK1, B and plasma cell signatures showed promise as viable approaches to treat SLE, pointing to their importance in SLE pathogenesis. Highlights: SLE transcripts defined 3 distinct clusters: interferon, inflammation, lymphocyte signaling. Interferon gene upregulation denoted hematological activity and vasculitis. Rs7918733 T > C was associated with upregulation of CASP7 in SLE patients. Druggability analysis suggested CTSL activity depression through proteasome inhibition.